2022
DOI: 10.18502/ssu.v30i9.11222
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Decreased Bone Density Prevalence in People with Common Risk Factors Referred to Al-Zahra Educational-Medical Center in Isfahan City Years of 2018 and 2019

Abstract: Introduction: Osteoporosis is a disease in skeletal system that is recognized by a lack of bone density and degeneration of bone tissue and can lead to increase the risk of bone fracture or even death. So, this study was conducted to determine the prevalence of decreased bone density in people with common risk factors referred to Al-Zahra Educational-Medical Center in Isfahan City years 2018-2019. Methods: This was a cross-sectional study. 3780 participants were included in the study by census sampling f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the present study, the variables of gender, history of a bone fracture in the past five years, and history of using glucocorticoids were identified as predicting risk factors of osteoporosis in older adults. On a similar note, in a study by Mousavi et al [ 32 ], gender, use of cortisone, and having a history of a bone fracture after the age of 40 were found to have a significant correlation with bone density. As with the present study, many other studies have confirmed the correlation between being female and an increased risk of osteoporosis [ 5 , 30 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In the present study, the variables of gender, history of a bone fracture in the past five years, and history of using glucocorticoids were identified as predicting risk factors of osteoporosis in older adults. On a similar note, in a study by Mousavi et al [ 32 ], gender, use of cortisone, and having a history of a bone fracture after the age of 40 were found to have a significant correlation with bone density. As with the present study, many other studies have confirmed the correlation between being female and an increased risk of osteoporosis [ 5 , 30 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 59%
“…The present study’s findings showed that the variables of smoking and drug abuse weren’t identified as predicting risk factors of osteoporosis in older adults. Similarly, a study by Mousavi et al reported that smoking did not correlate with osteoporosis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%